DISTANCE EDUCATION: ESSENCE AND PROBLEMS - Lakhtionova, Liudmyla (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The essence of distance learning is considered in accordance with the normative legal acts of Ukraine. Issues related to the content of this concept are highlighted.